A randomized phase II trial to compare safety and immunogenicity of the MVA-BN smallpox vaccine at various doses in adults with a history of AIDS. Issue 11 (4th March 2020) - Overton, Edgar Turner; Lawrence, Steven J.; Stapleton, Jack T.; Weidenthaler, Heinz; Schmidt, Darja; Koenen, Brigitte; Silbernagl, Günter; Nopora, Katrin; Chaplin, Paul
Highlights: No safety concerns were identified with MVA-BN in individuals with a history of AIDS. This immunocompromised population had no reports of myo- or pericarditis. Doubling the MVA-BN standard dose had no beneficial effect on the humoral response. Standard MVA-BN dose induced an immune response previously associated with protection. Abstract: Traditional replicating smallpox vaccines are associated with serious safety concerns in the general population and are contraindicated in immunocompromised individuals. However, this very population remains at greatest risk for severe complications following viral infections, making vaccine prevention particularly relevant. MVA-BN was developed as a non-replicating smallpox vaccine that is potentially safer for people who are immunocompromised. In this phase II trial, 3 MVA-BN dosing regimens were evaluated for safety, tolerability, and immunogenicity in persons with HIV (PWH) who had a history of AIDS. Following randomization, 87 participants who were predominately male and African American received either 2 standard doses on weeks 0 and 4 in the standard dose (SD) group (N = 27), 2 double-standard doses on the same schedule in the double dose (DD) group (N = 29), or 3 standard doses on weeks 0, 4 and 12 in the booster dose (BD) group (N = 31). No safety concerns were identified, and injection site pain was the most commonly reported solicited adverse event (AE) in all groups (66.7%), with no meaningful differences between groups. The incidence of severe (Grade 3) AEs was low across groups and no serious AEs or AEs of special interest considered related to study vaccine were reported. Doubling the standard MVA-BN dose had no significant effect on induction of neutralizing antibodies, with 100% seroconversion and comparable GMTs at week 6 in the SD and DD groups (78.9 and 100.3, respectively). A booster dose significantly increased peak neutralizing titers in the BD group (GMT: 281.1), which remained elevated at 12 months (GMT: 45.3) compared to the SD (GMT: 6.2) and DD (GMT: 10.6) groups. However, based on the immune response previously reported for healthy participants, a third dose (booster) does not appear necessary, even for immunocompromised participants. Clinical Trial Registry Number : NCT02038881.